Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1038/s41598-019-52269-4
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Extensional Rheology in Bolus Control during Swallowing

Abstract: Thickened fluids are commonly used in the medical management of individuals who suffer swallowing difficulty (known as dysphagia). Previous studies have shown that the rheological properties of a liquid affect the flow behavior of the bolus in swallowing, such as pharyngeal transit time. While there is no doubt that shear rheology is a highly important factor for bolus flow, it is suspected that extensional properties of a liquid bolus also plays an important role in swallowing, due to elongation of the bolus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 33 publications
3
32
0
Order By: Relevance
“…Similarly, a second study with videofluoroscopic observations in healthy subjects ( n = 8, age range: 22–30 year.) showed significant differences in pharyngeal transport time only between IDDSI Levels 1 and 4 ( p < 0.01) [ 44 ]. The small sample size is an important limitation in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a second study with videofluoroscopic observations in healthy subjects ( n = 8, age range: 22–30 year.) showed significant differences in pharyngeal transport time only between IDDSI Levels 1 and 4 ( p < 0.01) [ 44 ]. The small sample size is an important limitation in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, thin, elastic and cohesive liquids give rise to a moderate expansion upon leaving the in vitro oral cavity (die swell) that partly counteracts the elongation induced by gravity and result in a smooth and compact bolus shape, characterized by a lower bolus elongation. Recent in vivo results 29 provide a first confirmation of the potential benefit on bolus coherence in the pharynx of fluids with some level of extensional viscosity, but further in vivo studies should confirm this effect for fluids with stronger exten- sional properties. Liquids with similar steady shear rheology show a similar dynamics when leaving the in vitro oral cavity, but a more compact bolus is observed when the relaxation time and the filament breakage time in extension are higher.…”
Section: Liquid Samplementioning
confidence: 96%
“…In 2019, Hadde and Chen (2019) hypothesized that the extensional viscosity of the fluid affects the bolus flow and is related to cohesiveness of the fluid. In that same year, Hadde, Cichero, Zhao, Chen, and Chen (2019) confirmed the relevance of the extensional viscosity to bolus swallowing. The ratio of length to the width of the bolus during Upper Esophageal Sphincter (UES) opening were measured under lateral view of videofluoroscopy swallow study (VFSS) of eight healthy individuals.…”
Section: Thickened Fluidsmentioning
confidence: 80%
“…It was reported that a fluid of higher extensional viscosity generally has a lower bolus aspect ratio than a fluid of lower extensional viscosity. This shows that extensional viscosity reduces the elongation of the bolus in the pharyngeal phase during swallowing, thus potentially reduced the risk of post‐swallow residue due to bolus breakage (Hadde et al, 2019). On a related topic, Patel et al (2019) showed that fluids thickened with xanthan gum based thickener (i.e., high extensional viscosity) produced a significantly shorter bolus elongation at the pharyngeal stage compared to the starch based thickener.…”
Section: Thickened Fluidsmentioning
confidence: 99%